Interdisciplinary Interation in Design-Relation Between Graphic and Interior Design - Kutlu, Rana (Science Publishing Group, New York, USA, 2016)
Nowadays the concept of “identity” is worked on diligently as a marketing strategy and deemed as an important tool in concept works of design disciplines of different scales through physical space, which reaches out to consumers. In this study, through the literature review, impacts of identity on spatial design are discussed in terms of interdisciplinary communication and tools used for transferring the meaning, which transforms identity into image are listed. Besides, the impact of spatial design on users’ perception is explained in connection with graphic design, architecture and interior architecture. Tools used for meaning transfer, which play a role in defining and developing design based on identity, are evaluated together with identity and image creating processes.
Keywords: Space; Graphic Design; Interdisciplinary Interaction; Relevance to Design Practice